IMPLEMENTASI PEMBELAJARAN LITERASIDALAM MENINGKATKAN MINAT MEMBACA PESERTA DIDIK DI KELAS IV SD NEGERI 136916 TANJUNG BALAI - Rahman, Abdul; Harahap, Siti Kholijah; Nursyaidah, Nursyaidah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2023)
Developments in the field of education are a means or forum for developing Human Resources (HR). Education is not only defined as the transformation of knowledge but also includes the transformation of culture and values that develop in society, in order to produce quality students who can develop every potential that students have which is obtained through the learning process and implementing habits that can increasing students’ interest in learning, especially students’ interest in reading in literacy learning, thus implementing literacy learning to increase students’ interest in reading. This research uses a qualitative approach with descriptive methods. The research subjects were 28 people consisting of 15 male students and 13 female students. Based on researchers’ observations of real conditions in the field, students’ interest in learning can have a positive impact on students’ learning outcomes and students’ responsiveness. Students’ lack of reading interest in reading and understanding the content of students’ reading texts in concluding paragraphs is a problem for students in determining the main idea of reading text paragraphs. To overcome this problem, there are several efforts that teachers can make to increase students’ interest in learning. The efforts that teachers can provide are implementing literacy learning in class IV of SD Negeri 136916 Tanjungbalai, with the implementation it will help students increase their interest in learning, so that they can make students more enthusiastic about learning, processing with maximum marks and preparing plans. Based on the results of the diagnosis, namely by providing group study guidance. Next, the final effort is to provide assistance by asking parents for guidance in supervising students while studying at home and providing motivation so as to foster students’ interest in learning. Keywords: Implementation; Literacy; Interest in Reading.